Neurological outcome and quality of life 3 months after COVID‐19: A prospective observational cohort study - Rass, Verena; Beer, Ronny; Schiefecker, Alois Josef; Kofler, Mario; Lindner, Anna; Mahlknecht, Philipp; Heim, Beatrice; Limmert, Victoria; Sahanic, Sabina; Pizzini, Alex; Sonnweber, Thomas; Tancevski, Ivan; et al. (European journal of neurology, 2021)
Background and purpose To assess neurological manifestations and health‐related quality of life (QoL) 3 months after COVID‐19. Methods In this prospective, multicenter, observational cohort study we systematically evaluated neurological signs and diseases by detailed neurological examination and a predefined test battery assessing smelling disorders (16‐item Sniffin Sticks test), cognitive deficits (Montreal Cognitive Assessment), QoL (36‐item Short Form), and mental health (Hospital Anxiety and Depression Scale, Posttraumatic Stress Disorder Checklist–5) 3 months after disease onset. Results Of 135 consecutive COVID‐19 patients, 31 (23%) required intensive care unit (ICU) care (severe), 72 (53%) were admitted to the regular ward (moderate), and 32 (24%) underwent outpatient care (mild) during acute disease. At the 3‐month follow‐up, 20 patients (15%) presented with one or more neurological syndromes that were not evident before COVID‐19. These included polyneuro/myopathy (n = 17, 13%) with one patient presenting with Guillain‐Barré syndrome, mild encephalopathy (n = 2, 2%), parkinsonism (n = 1, 1%), orthostatic hypotension (n = 1, 1%), and ischemic stroke (n = 1, 1%). Objective testing revealed hyposmia/anosmia in 57/127 (45%) patients at the 3‐month follow‐up. Self‐reported hyposmia/anosmia was lower (17%) at 3 months, however, improved when compared to the acute disease phase (44%; p < 0.001). At follow‐up, cognitive deficits were apparent in 23%, and QoL was impaired in 31%. Assessment of mental health revealed symptoms of depression, anxiety, and posttraumatic stress disorders in 11%, 25%, and 11%, respectively. Conclusions Despite recovery from the acute infection, neurological symptoms were prevalent at the 3‐month follow‐up. Above all, smelling disorders were persistent in a large proportion of patients. Three months after COVID‐19, 20/135 patients (15%) presented with one or more neurological syndromes that were not evident before disease onset. Objective testing revealed hyposmia/anosmia in 45% of patients at the 3‐month follow‐up in comparison to 17% who reported hyposmia/anosmia. Cognitive deficits were apparent in 23%, quality of life was impaired in 31%, depression was found in 11%, anxiety in 25% and posttraumatic stress disorders in 11%.